190km Φ-OTDR with bidirectional Raman and relay erbium-doped fiber hybrid amplification. (July 2023) - Wang, Yuang; Wang, Yu; He, Chunchen; Liu, Xin; Bai, Qing; Jin, Baoquan
Highlights: A long-distance coherent detection Φ-OTDR scheme with bidirectional Raman and relay erbium-doped fiber hybrid amplification is proposed. The ultra-long Φ-OTDR system with 190 km sensing distance and 22 m spatial resolution is realized. Multi-point vibration signals are located and restored where RBS signals are relatively weak. Abstract: In this paper, a long-distance coherent detection phase-sensitive optical time-domain reflectometer (Φ-OTDR) scheme with bidirectional Raman and relay erbium-doped fiber hybrid amplification is proposed. The bidirectional Raman pump light acting on the erbium-doped fiber (EDF) can realize the passive amplification of pulsed signal light and Rayleigh backward scattering (RBS) light at the same time. The scheme utilizes bidirectional 1455 nm pumps as the pump source of relay amplification to achieve a longer sensing distance. Experimental results demonstrate that, an ultra-long Φ-OTDR system with 190 km sensing distance and 22 m spatial resolution is realized. Multi-point vibration signals are located and restored at 69.67 km, 120.13 km and 190.79 km, respectively. The average signal-to-noise ratio (SNR) of positioning curve is 10.32 dB, the average SNR of demodulated phase signal is 26.02 dB, and the frequency response range is from 5 Hz to 150 Hz. Furthermore, the sensing system has good linear characteristics of phase demodulation with a correlation coefficient of 0.997. The actual disturbance events are also detected at the far-end of sensing fiber. To the best of our knowledge, this system achieves the longest-distance Φ-OTDR without relay power supply. This passive hybrid amplification method can avoid the intermediate power supply along sensing fiber, which provides a reference for long-distance vibration monitoring of Φ-OTDR system.